Evolution of genetic architecture and gene regulation in biphenyl/PCB-degrading bacteria - Fujihara, Hidehiko; Hirose, Jun; Suenaga, Hikaru (Frontiers in Microbiology, 2023)
A variety of bacteria in the environment can utilize xenobiotic compounds as a source of carbon and energy. The bacterial strains degrading xenobiotics are suitable models to investigate the adaptation and evolutionary processes of bacteria because they appear to have emerged relatively soon after the release of these compounds into the natural environment. Analyses of bacterial genome sequences indicate that horizontal gene transfer (HGT) is the most important contributor to the bacterial evolution of genetic architecture. Further, host bacteria that can use energy effectively by controlling the expression of organized gene clusters involved in xenobiotic degradation will have a survival advantage in harsh xenobiotic-rich environments. In this review, we summarize the current understanding of evolutionary mechanisms operative in bacteria, with a focus on biphenyl/PCB-degrading bacteria. We then discuss metagenomic approaches that are useful for such investigation.